Summary of the AAPM task group 248 report: Interoperability assessment for the commissioning of medical imaging acquisition systems. Issue 7 (1st June 2019) - Walz‐Flannigan, Alisa; Weiser, John; Goode, Allen R.; Junck, Kevin; Tarbox, Lawrence; Dave, Jaydev K.; Clunie, David A.; McColl, Roderick W.; Langer, Steve G.
Abstract : Purpose: We summarize the AAPM TG248 Task Group report on interoperability assessment for the commissioning of medical imaging acquisition systems in order to bring needed attention to the value and role of quality assurance testing throughout the imaging chain. Methods: To guide the clinical physicist involved in commissioning of imaging systems, we describe a framework and tools for incorporating interoperability assessment into imaging equipment commissioning. Results: While equipment commissioning may coincide with equipment acceptance testing, its scope may extend beyond validation of product or purchase specifications. Equipment commissioning is meant to provide assurance that a system is ready for clinical use, and system interoperability plays an essential role in the clinical use of an imaging system. Conclusion: The functionality of a diagnostic imaging system extends beyond the acquisition console and depends on interoperability with a host of other systems such as the Radiology Information System, a Picture Archive and Communication System, post‐processing software, treatment planning software, and clinical viewers.